2012
DOI: 10.1111/aas.12047
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of post‐dural puncture headache in parturients: a systematic review and meta‐analysis

Abstract: Post-dural puncture headaches (PDPHs) present an important clinical problem. We assessed methods to decrease accidental dural punctures (ADPs) and interventions to reduce PDPH following ADP. Multiple electronic databases were searched for randomised clinical trials (RCTs) of parturients having labour epidurals, in which the studied intervention could plausibly affect ADP or PDPH, and the incidence of at least one of these was recorded. Forty RCTs (n = 11,536 epidural insertions) were included, studying combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 70 publications
0
52
0
2
Order By: Relevance
“…Therefore, the use of a prophylactic epidural blood patch might prevent PDPH and the need for further treatments in that regard. However, recent systemic reviews with a meta-analysis of four randomized controlled studies have not conclusively supported the use of a prophylactic epidural blood patch for preventing PDPH [4445]. Three of the four randomized controlled studies analyzed in these systemic reviews found a statistical difference in PDPH incidence.…”
Section: Invasivementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the use of a prophylactic epidural blood patch might prevent PDPH and the need for further treatments in that regard. However, recent systemic reviews with a meta-analysis of four randomized controlled studies have not conclusively supported the use of a prophylactic epidural blood patch for preventing PDPH [4445]. Three of the four randomized controlled studies analyzed in these systemic reviews found a statistical difference in PDPH incidence.…”
Section: Invasivementioning
confidence: 99%
“…This procedure allows immediate analgesia during labor through the intrathecal catheter, negating the risk of repeated dural punctures [505152]. Systematic reviews [444553] have indicated that intrathecal catheter placement does not significantly reduce the incidence of PDPH. However, this intervention does reduce the overall severity of PDPH and the need for an epidural blood patch.…”
Section: Invasivementioning
confidence: 99%
“…Selection of an appropriate length 20-22 gauge, atraumatic spinal needle can reduce the risk of a post-LP headache. 40,41 As the spinal needle is inserted through the skin, resistance should be encountered as the needle traverses the dense supraspinous and interspinous ligaments. Despite careful site marking, minor needle redirections are often needed to advance the spinal needle into the spinal canal.…”
Section: Ultrasound-guided Site Markingmentioning
confidence: 99%
“…Paech et al concluded that anaesthetists should attempt to administer 20 ml autologous blood, limited by back pain, based on their trial [6]. Some authors have advocated prophylactic epidural blood patch after accidental dural puncture, and a number of reviews have looked at this area, concluding that previous studies were flawed in their methodology and further large studies were required [25,26]. One hundred and sixteen parturients were randomly assigned by Stein et al to receive either prophylactic or therapeutic epidural blood patch with 15-20 ml autologous blood after accidental dural puncture [27].…”
Section: Discussionmentioning
confidence: 99%